Elastic and magnetoelastic relaxation behaviour of multiferroic (ferromagnetic + ferroelectric + ferroelastic) Pb(Fe0.5Nb0.5)O3 perovskite. (30th June 2015) - Carpenter, M A; Schiemer, J A; Lascu, I; Harrison, R J; Kumar, A; Katiyar, R S; Ortega, N; Sanchez, D A; Mejia, C Salazar; Schnelle, W; Echizen, M; Shinohara, H; et al.
Abstract: Resonant Ultrasound Spectroscopy has been used to characterize elastic and anelastic anomalies in a polycrystalline sample of multiferroic Pb(Fe0.5 Nb0.5 )O3 (PFN). Elastic softening begins at 550 K, which is close to the Burns temperature marking the development of dynamical polar nanoregions. A small increase in acoustic loss at 425 K coincides with the value of T * reported for polar nanoregions starting to acquire a static or quasi-static component. Softening of the shear modulus by 30–35% through 395–320 K, together with a peak in acoustic loss, is due to classical strain/order parameter coupling through the cubic → tetragonal → monoclinic transition sequence of ferroelectric/ferroelastic transitions. A plateau of high acoustic loss below 320 K is due to the mobility under stress of a ferroelastic microstructure but, instead of the typical effects of freezing of twin wall motion at some low temperature, there is a steady decrease in loss and increase in elastic stiffness below 85 K. This is attributed to freezing of a succession of strain-coupled defects with a range of relaxation times and is consistent with a report in the literature that PFN develops a tweed microstructure over a wide temperature interval. No overt anomaly was observed near the expected Néel point, 145 K, consistent with weak/absent spin/lattice coupling but heat capacity measurements showed that the antiferromagnetic transition is actually smeared out or suppressed. Instead, the sample is weakly ferromagnetic up to 560 K, though it has not been possible to exclude definitively the possibility that this could be due to some magnetic impurity. Overall, evidence from the RUS data is of a permeating influence of static and dynamic strain relaxation effects which are attributed to local strain heterogeneity on a mesoscopic length scale. These, in turn, must have a role in determining the magnetic properties and multiferroic character of PFN.